2019
DOI: 10.1051/e3sconf/201913801011
|View full text |Cite
|
Sign up to set email alerts
|

Water-resistant fiber-reinforced gypsum cement-pozzolanic composites

Abstract: Gypsum and gypsum-cement-pozzolanic composites are of significant interest as materials and products for building decoration. The current tendency to reduce the consumption of gypsum-based materials and products in the context of growth and development of the finishing materials market depends on the decrease in their competitiveness compared to peers. This leads to significant interest in improving the quality of products based on gypsum and gypsum-cement-pozzolanic binder. Dispersed reinforcement is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Such a composition was called gypsum-cement-pozzolanic binders (Magallanes-Rivera et al, 2012; Volzhensky et al, 1969;Çolak, 2002). Studies have shown that the most stable composition consists of a gypsum binder, Portland cement, and an appropriate amount of active mineral additives, which is called gypsumcement-pozzolanic binders (Mukhametrakhimov et al, 2019;Potapova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such a composition was called gypsum-cement-pozzolanic binders (Magallanes-Rivera et al, 2012; Volzhensky et al, 1969;Çolak, 2002). Studies have shown that the most stable composition consists of a gypsum binder, Portland cement, and an appropriate amount of active mineral additives, which is called gypsumcement-pozzolanic binders (Mukhametrakhimov et al, 2019;Potapova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to increase water resistance of gypsum binder in various ways [14][15][16][17][18][19][20]. The simplest and, at the same time, effective, is creation of mixed gypsum binders.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recently, scientists have been working on the search for effective pozzolanic materials from thermally activated polymineral clays with a low content of kaolinite and its complete absence [4][5][6]. At the same time, it was found that the combined use of polymineral clays with carbonate additives leads to the emergence of a synergistic effect, expressed in an increase in technical and operational parameters of obtained materials [7][8][9][10][11][12][13][14][15]. Complex additives which differ by presence of a synergetic effect in the cointroduction of multiple mineral additives are of great importance while the creation of blended cements [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…XRD pattern of blended cement stone sample with 20 % of complex additive based on calcined kaolinitic clay and limestone.The diffractogram indicates a large presence of carboaluminate phases. There is a complete transition of calcium hydromonosulfoaluminate (3CaO • Al2O3 • CaSO4 • (11-12) H2O) in Portland cement on the CaCO3 particles surface into calcium hydromonocarboaluminates (3CaO • Al2O3 • CaCO3 • (11-12) H2O)[12] with interplanar distances d = (4.267; 4.167; 3.661; 3.521; 3.117; 2.653) Å[10]. It should be noted that the limestone amount and its activity are sufficient for the entire hydrosemicarboaluminate (3СаО • Al2O3 • 0.5CaСO3 • (11-12) H2O) to turn into calcium hydrogen monocarboaluminate[11].In the composition of the blended cement stone with the complex additive, there is a small content of ettringite (d = (9.718; 5.646) • Å), approximately the same as in the control composition.…”
mentioning
confidence: 99%